MOBILE HEALTH APPLICATION – SMARTPHONE BASED DALAM PENINGKATAN SELF-MANAGEMENT PASIEN DIABETES MELITUS - Made Yashinta Yashinta Maharani; Rr. Tutik Sri Hariyati; I Wayan Sukawana (Jurnal Gema Keperawatan, 2018)
ABSTRACTTechnological innovation mHealth Application (Apps), namely software on smartphones or tablets can be used for self-management in patients with diabetes mellitus. This study aims to determine the potential for developing mobile health applications on smartphones to improve self-management of patients with diabetes mellitus. The method used is the study of literature. Smartphone-based mHealth applications include independent blood sugar control, medication, diet, physical activity, weight control, blood pressure control, and education on diabetes self-management proved to be effective in improving self-management of diabetics. Mobile health applications based on smart phones is one solution to improve self-management so that it can improve the health status of diabetic patients.